Deteksi Cryptosporidium sp. dengan Pewarnaan Modifikasi Tahan Asam pada Tinja Siswa SDN X Kecamatan Rumbai, Pekanbaru - Esy Maryanti; Hayatul Rahmi; Suri Dwi Lesmana; Lilly Haslinda (Fakultas Kedokteran Universitas Riau, 2014)
Oportunistic intestinal protozoa infection caused by Cryptosporidium sp is a public health problem inimmunocompromise individual and children. Cryptosporidiosis is a disease caused by Cryptosporidium sp whichconsidered a cause of emerging and opportunistic infection. Cryptosporidium sp. are single cell of coccidian caninfected human and animals. This study was to detect Cryptosporidium sp with method of staining acid-resistantmodification among elementary school children of SDN X Kecamatan Rumbai Kota Pekanbaru. Stool examinationof 94 samples were obtained two (2,1%) samples were found with Cryptosporidium sp.